SISKEUDES for Transparency and Accountability in Village Financial Management: SISKEUDES untuk Transparansi dan Akuntabilitas Pengelolaan Keuangan Desa - Azizah Zaniana Manik; Annio Indah Lestari Nasution; Yenni Samri Juliati Nasution (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Village governments in Indonesia play a strategic role in managing public finances to support local development, yet manual financial reporting often results in inefficiency, errors, and weak accountability. Background (Specific): To address this, the Indonesian Financial and Development Supervisory Agency (BPKP) introduced the Village Financial System (SISKEUDES) as a digital tool for financial planning, execution, and reporting. Knowledge Gap: While prior studies confirm SISKEUDES’ benefits in digitally advanced regions, its effectiveness in rural areas with limited infrastructure and low digital literacy remains underexplored. Aim: This study examines the role of SISKEUDES in enhancing the quality, effectiveness, and accountability of financial management in Lae Nuaha Village. Results: Findings show that SISKEUDES improved report quality through greater relevance, reliability, comparability, and understandability; reduced reporting duration from two weeks to three days; and strengthened accountability both vertically to government authorities and horizontally to the village community. Novelty: Unlike existing research, this study highlights implementation in a low-resource context, revealing that digitalization remains effective despite infrastructure and literacy challenges. Implications: The study contributes to good governance and new public management discourse, offering practical insights for policymakers to expand SISKEUDES with supportive infrastructure and capacity building in rural areas.Highlight : SISKEUDES improves village financial report quality. Reporting becomes faster and more effective. Accountability increases to government and community Keywords : SISKEUDES, Village Finance, Financial Report Quality, Effectiveness, Accountability